Hos vem hör jag hemma? Frigörelse, beroende och narcissistisk problematik hos tonårsdöttrar och fäder i ungdomslitteratur - Andræ, Marika (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2006)
Is it possible to characterize young adults as a homogeneous group with distinct attitudes towards their parents? This article provides examples of theories of psychology and sociology which indicate a flawed relationship between teenage daughters and their fathers. The primary material examined is a couple of contemporary Swedish novels for young adults. Within these stories, we get a picture of a relationship more denoted by gender patterns than child and parent opposition. One theory of young adults' problems today is the thesis of a "narcissistic" approach that makes the process of becoming an adult more difficult. This article shows how the postulations of the theory changes, when gender and power is included. In the fiction studied, the daughters are more mature than their fathers, which makes the separation and dependence pattern distinct from the traditional view of the child/parent relationship.